The Influence of Knowledge Management on the Performance Through the Competitive Advantages of Polytechnics in Indonesia - R. Elly Mirati, Zulkifli,Tri Widyastuti, Erwin Permana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to analyze: 1) the influence of knowledge management on the performance of Polytechnics, 2) the influence of knowledge management on the competitive advantage of Polytechnics, 3) the influence of competitive advantage on the performance of Polytechnics. Analytical techniques use Structural Equation Model (SEM) with SmartPLS. The data was collected through the dissemination of questionnaires. The research respondents were the chairman of the head study program, the head of the department, and the deputy director at six polytechnics in Indonesia. The results of the analysis show that knowledge management affects competitive advantage; competitive advantage affects performance; knowledge management does not affect the performance of polytechnics. Statistical test results show that all constructs of model builders are at a high level. The influence of knowledge management on performance is greater when it uses competitive advantages and is not significant when it is direct on performance. Based on the results of this study, it is recommended that Polytechnics always increase the competitive advantage. In the future, research involving more specific and detailed variables is needed to test the competitive advantage and performance of Polytechnics such as digital infrastructure, and their impacts on the sustainability of Polytechnic competitive advantage.